Taxes, Theft, and Firm Performance - MIRONOV, MAXIM (Journal of Finance, 2013)
ABSTRACT This paper examines the interaction between income diversion and firm performance. Using unique Russian banking transaction data, I identify 42,483 spacemen, fly‐by‐night firms created specifically for income diversion. Next, I build a direct measure of income diversion for 45,429 companies and show that it is negatively related to firm performance. I identify the main reason for the observed effect as managerial diversion rather than tax evasion per se. I further show that stricter tax enforcement can improve firm performance: a one standard deviation increase in tax enforcement corresponds to an increase in the annual revenue growth rate of 2.6%.